Isolation, Identification and Characterization of Highly Tellurite-Resistant, Tellurite-Reducing Bacteria from Antarctica - Vasquez-Guzman, C; Arenas-Salinas, F; Muñoz-Villagran, C; Díaz-Vásquez, W; Pugin, B (2014)
Sin Editorial Disponible